Financial wellbeing of older workers following injury – research utilising Statistics New Zealand’s Integrated Data Infrastructure: IJPDS (2017) Issue 1, Vol 1:102, Proceedings of the IPDLN Conference (August 2016) - Davie, Gabrielle; Lilley, Rebbecca (International Journal of Population Data Science, 2017)
ABSTRACT Objectives 1. To undertake epidemiological analyses of New Zealand’s newly available linked longitudinal administrative data on financial wellbeing outcomes in older workers to understand the implications of injury in an ageing workforce 2. To gain an understanding of Statistics NZ’s Integrated Data Infrastructure (IDI) to inform the future use of the IDI specifically for health research Approach The impact of injury on the income of older workers was quantified by comparing financial well-being outcomes for injured and non-injured older workers over a 3 year period using IDI linked records on: i) injury claims; ii) personal taxation records; and iii) benefit receipt. Older workers were identified as all individuals aged 45 years and over in 2009 who had employment related tax payments in the previous year. Anyone with injury prior to 2009 for which earnings-related compensation was still being received in 2009 was excluded. Those that had an entitlement claim accepted by NZ’s Accident Compensation Corporation (ACC) for an injury that occurred in 2009 were defined as injured older workers, the remainder were considered non-injured. Date of injury was used as the reference date from which to calculate financial outcomes for injured older workers; non-injured workers were randomly assigned a date in 2009. Financial wellbeing, assessed by total earnings (income from wages and salary, employment related compensation from ACC and benefit receipt), was compared between injured and non-injured older workers at 1, 2 and 3 years following the reference date. Potential explanatory variables, such as gender, region of residency, and previous income/earnings received, was examined in multi-variable analyses. Results From individually linked records in the IDI, considerable data management was required to identify those that met the criteria for injured and non-injured older workers. Preliminary analyses indicate total earnings at all 3 time periods differ between older workers that are injured and those that aren’t. Breakdown of total earnings by source of income sheds light on some of these differences. Observed differences are not consistent between each 5-year age group. Conclusions The outcomes of injury are multi-faceted. The impact of injury on the financial well-being of older workers is concerning given NZ’s comprehensive universal injury compensation and welfare systems. The ability to use individually-linked longitudinal administrative records from Government agencies made this research possible, although using the IDI was not without its challenges.